High fat diet and endurance exercise performance - Higashida, K.; Higuchi, M. (Sports Performance, 2015)
The high carbohydrate diet has been a popular dietary intervention among endurance athletes for many years, because the depletion of muscle glycogen is associated with fatigue during endurance exercise. Therefore, numerous studies regarding carbohydrate supplementation and exercise regimens have been done and have demonstrated the association between muscle glycogen and performance in endurance exercise. These results strongly suggest the importance of maximizing muscle glycogen stores before the initiation of exercise to allow the athlete to have an optimal endurance performance. On the other hand, high fat diet intervention is not popular, although it has been reported that a high fat diet induces an increase in mitochondrial biogenesis in skeletal muscle and enhances endurance performance in animal studies. Therefore, the purpose of this article is to consider the evidence that an increased in fat intake is beneficial for endurance performance.